Exploration of Religious Music Art in Pekalongan: Transformation of Tradition, Digitalization, and Role in Contemporary Preaching - Perdana, Firdaus (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
Religious music art in Pekalongan faces significant challenges in maintaining tradition amidst modernization and digitalization. This study explores the transformation of religious music art in Pekalongan in the context of tradition, adaptation to the digital era, and its role as a contemporary da’wah medium. The study used a qualitative approach with a descriptive exploratory method. Data were collected through in-depth interviews with artists, religious figures, and cultural observers, as well as observation and documentation of religious art events in Pekalongan. Data analysis was carried out thematically concerning the theory of artistic communication, socio-cultural modernization, and digital media. The study results show that religious music art in Pekalongan has transformed from traditional forms such as rebana and hadroh into a modern format that combines elements of tradition with digital technology. Digitalization provides excellent opportunities for developing and disseminating this art through platforms such as YouTube and TikTok. However, it still faces challenges such as commercialisation and the risk of losing the essence of tradition. Religious music art in Pekalongan has also proven effective as a contemporary da’wah medium, especially for the younger generation, through Islamic lyrics and culturally relevant formats. This transformation shows the balance between preserving tradition and modern innovation, making religious music a cultural identity and a dynamic tool for preaching.